Community use of oral antibiotics transiently reprofiles the intestinal microbiome in young Bangladeshi children - Andrew Baldi; Sabine Braat; Mohammed Imrul Hasan; Cavan Bennett; Marilou Barrios; Naomi Jones; Gemma Moir-Meyer; Imadh Abdul Azeez; Stephen Wilcox; Mohammad Saiful Alam Bhuiyan; Ricardo Ataide; Danielle Clucas; et al. (Nature Communications, 2024)
Abstract Antibiotics may alter the gut microbiome, and this is one of the mechanisms by which antimicrobial resistance may be promoted. Suboptimal antimicrobial stewardship in Asia has been linked to antimicrobial resistance. We aim to examine the relationship between oral antibiotic use and composition and antimicrobial resistance in the gut microbiome in 1093 Bangladeshi infants. We leverage a trial of 8-month-old infants in rural Bangladesh: 61% of children were cumulatively exposed to antibiotics (most commonly cephalosporins and macrolides) over the 12-month study period, including 47% in the first 3 months of the study, usually for fever or respiratory infection. 16S rRNA amplicon sequencing in 11-month-old infants reveals that alpha diversity of the intestinal microbiome is reduced in children who received antibiotics within the previous 7 days; these samples also exhibit enrichment for Enterococcus and Escherichia/Shigella genera. No effect is seen in children who received antibiotics earlier. Using shotgun metagenomics, overall abundance of antimicrobial resistance genes declines over time. Enrichment for an Enterococcus-related antimicrobial resistance gene is observed in children receiving antibiotics within the previous 7 days, but not earlier. Presence of antimicrobial resistance genes is correlated to microbiome composition. In Bangladeshi children, community use of antibiotics transiently reprofiles the gut microbiome.